OPTIMASI ANALISIS AMILASE DAN GLUKANASE YANG DIEKSTRAK DARI MISELIUM Pleurotus ostreatus DENGAN ASAM 3,5 DINITROSALISILAT - Maman Rahmansyah; I Made Sudiana (The East Java Biological Society, 2003)
Enzymatic activities of amylase (1.4-α-D-glucan glucano hydrolase) and glucanase (1.4-β-glucanase) that extracted from Pleurotus ostreatus mycelium determined through the reducing sugar accumulation. The enzymes assayed in amorphous cellulose (carboxymethylcellulose = CMC) and starch substrate, respectively. Complexity reaction of the sugar to DNS (3.5-dinitrosalicylic acid) become sensitive caused of adding up oxidative agent of sodium sulfite and phenol. Variation in substrate concentration, combine with incubation period and its temperature was able to promote optimum activities of amylase enzymes. The best possible activity of amylase was turn out on 25° C temperature incubation along 20 minutes in 5% starch substrate assessment. Incubation period more then 60 minutes on amylase and cellulase caused those activities leaved to 40 and 70% down, correspondingly. Modified DNS fastened on reducing sugar twice effectively compared to unmodified one.